PENERAPAN PEMBELAJARAN BERDIFERENSIASI UNTUK MENGATASI KECEMASAN BERBICARA DI DEPAN UMUM PADA MATERI PIDATO SISWA KELAS VIII.3 SMP N 7 DENPASAR - I Dewa Dode Agus Adi Pranatha; I Nyoman Adi Susrawan; Ni Nyoman Ardiani (Journal of Innovation Research and Knowledge, 2026)
This study aims to overcome public speaking anxiety (speech anxiety) and improve speech practice skills through the implementation of differentiated learning processes in class VIII.3 students of SMP Negeri 7 Denpasar. This Classroom Action Research (CAR) was conducted in two reflective and collaborative cycles with 39 students as research subjects. Data collection used a Likert scale questionnaire instrument to measure speech anxiety and a direct performance test to measure speech oral competence. The results showed a significant linear success in both main aspects: 1) Academic Aspect, the classical average value (Mean) of speech skills increased from 80.10 in Cycle I to 80.79 in Cycle II, and drastically boosted the percentage of classical learning completeness from 51.28% (Cycle I) to 92.31% (Cycle II); 2) Psychological Aspect, the classical average anxiety decreased sharply from the High category (27.26) in Pre-cycle, down to the Medium Category (53.44) in Cycle I, until reaching the lowest point of the psychological safe zone (46.51) in Cycle II, where 69.23% of the class population (27 students) were free from severe anxiety. The implications of this study prove that the expansion of tiered performance method variations (multi-tiered speaking methods) is able to dissolve the affective filters that interfere with working memory, so as to absolutely lead students to achieve mastery of oral speaking performance competence.